Standardizing the cardiac radioablation targeting workflow: enabling semi-automated angulation and segmentation of the heart according to the American Heart Association segmented model. (19th May 2022) - Van Der Ree, MH; Visser, J; Planken, RN; Dieleman, EMT; Boekholdt, SM; Balgobind, BV; Postema, PG
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Dutch Heart Foundation Purpose: Cardiac radioablation has evolved as a potential treatment modality for therapy-refractory ventricular tachycardia. To standardize cardiac radioablation treatments, promote accurate communication and target identification, and to assess toxicity, robust and reproducible methods for angulation and cardiac segmentation are paramount. In this study, we developed and evaluated a workflow for semi-automated angulation and segmentation according to the American Heart Association (AHA) 17-segment model. Methods and materials: The workflow for semi-automated angulation and segmentation of the planning-CT was based on an in-house developed tool requiring placement of only 4 point-markers and a rotation matrix. For angulation, 2 markers defining the cardiac long-axis were placed: at the cardiac apex and at the center of the mitral valve (figure A). A rotation matrix was derived that angulates the CT-volume, resulting in the cardiac short axis (figure B). Segmentation was subsequently performed based on marking the two left ventricular hinge points (figure BC). To evaluate reproducibility, 5 observers independently placed markers in planning-CTs of 6 patients. Results: The Root-Mean-Square of the standard deviation for the angulation and segmentation marker positions were all below 0.52cm. The 17-segments were subsequently generated and compared between the observers resulting in a median dice coefficient of 0.8 [0.70;0.87] and a median of the mean Hausdorff distance of 0.09cm [0.05;0.17]. Figure D shows the heat maps of two illustrative segments indicating the percentage agreement per voxel between the 5 observers. The interquartile ranges of Euler angles α and β, determined by the angulation markers, was less than 3 0 for all patients except one. For the γ angle, determined by the hinge point markers, the interquartile range was up to 12 0 . Conclusion: In this study, a workflow for cardiac radioablation is presented that enables reproducible semi-automatic cardiac angulation and segmentation of the planning-CT according to the AHA 17-segment model. This workflow can be easily implemented and be used to promote communication between radiation oncology and cardiology, enables cardiology-oriented targeting and permits focused toxicity evaluations.